KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS X SMK NEGERI 10 PADANG - Kurniadi, Rizal; Thahar, Harris Effendi; Basri, Irfani (Universitas Negeri Padang, 2018)
ABSTRACT This article was written to describe the correlation of reading comprehension skill with the skill of writing the text of the result of observation of the tenth grade students of SMK Negeri 10 Padang. This research is a quantitative research with correlational method. The sample in this study amounted to 30 people. The data of this research is the result score skill test reading comprehension and the result score skill test of writing the text of the result of observation. Based on data analysis and discussion, the following three things are obtained. First, the skill of reading comprehension of the tenth grade students of SMK Negeri 10 Padang is in good qualification (77,13). Second, the skill of writting the text of the result of observation of the tenth grade students of SMK Negeri 10 Padang is in more than enough qualification (69,63). Third, there is correlation of reading comprehension skill with the skill of writing the text of the result of observation of the tenth grade students of SMK Negeri 10 Padang because tcount>ttable (2,47>1,31). Kata kunci: korelasi, membaca pemahaman, menulis, teks laporan hasil observasi